A brighter future? Quantifying the rebound effect in energy efficient lighting - Joachim Schleich; Bradford Mills; Elisabeth Dütschke (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
This paper quantifies the direct rebound effects associated with the switch from incandescent lamps (ILs) or halogen bulbs to more energy efficient compact fluorescent lamps (CFLs) or light emitting diodes (LEDs) using a large nationally representative survey of German households. The direct rebound effect is measured as the elasticity of useful lighting demand with respect to changes in energy efficient lamps. In particular, the rebound effect is decomposed into changes in lamp luminosity and burn time. On average, more efficient replacement bulbs are 23% brighter and burn about 6.5 minutes per day longer than replaced bulbs. For the most frequent (modal) bulb switch, i.e. the replacement of the main bulb in the living or dining room, luminosity increases by 10% and burn time increases by 9 minutes per day. For the average bulb, the associated total direct rebound effect is estimated at 6.3%. The larger part (around 60%) of this rebound effect results from increases in bulb luminosity. For the modal bulb the total direct rebound effect is smaller at 2.6%, with around 60% attributable to an increase in burn time. Average and modal bulb differences suggest that the magnitude to the rebound effect may decrease with intensity of initial bulb use. The magnitude of the direct rebound and the relative contributions of changes in luminosity and burn time also tend to differ by initial bulb type and by replacement bulb type. Finally, about a third of the bulb switches entail a negative rebound effect, i.e. energy savings are larger than expected if luminosity and burn time remained unchanged, highlighting significant heterogeneity in household responses to the adoption of energy efficient bulbs.
Keywords: 330; rebound effect; lighting; energy efficiency; energy demand